Live digital theatre : interdisciplinary performative pedagogies - Dunđerović, Aleksandar Sasha (Routledge advances in theatre and performance studies, 2023)
"Live Digital Theatre explores the experiences of Interdisciplinary Performing Arts practitioners working on digital performance and in particular live digital theatre. Collaborating with world-leading practitioners - Kolectiv Theatre (UK), Teatro Os Satyros (Brazil), and The Red Curtain International (India)- this study investigates the ways to bring live digital performance into theatre training and performance making. The idea of Interdisciplinary Performative Pedagogies is placed within the context of the exploration of live digital theatre and is used to understand creative practices and how can one learn from these practices. The book presents a pedagogical approach to contemporary practices in digital performance; from interdisciplinary live performance using digital technology, to live Zoom theatre, YouTube, mixed media recorded and live performance. The book also combines a series of case studies and pedagogical practices on live digital performance and intermedial theatre. This book will be of great interest to students and scholars in performing arts, digital arts, media, and gaming"--